2014
DOI: 10.1109/tcsi.2013.2284184
|View full text |Cite
|
Sign up to set email alerts
|

A Multicast Tree Router for Multichip Neuromorphic Systems

Abstract: Abstract-We present a tree router for multichip systems that guarantees deadlock-free multicast packet routing without dropping packets or restricting their length. Multicast routing is required to efficiently connect massively parallel systems' computational units when each unit is connected to thousands of others residing on multiple chips, which is the case in neuromorphic systems. Our tree router implements this one-tomany routing by branching recursively-broadcasting the packet within a specified subtree.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…Many years have passed since the first publication on neuromorphic electronic systems [11], and remarkable progress has been made by the small but vibrant Neuromorphic Engineering (NE) community [162], [163]. For example the NE community has mastered the art of building real-time sensory-motor reactive systems, by interfacing circuits and networks of the type described in this paper with neuromorphic event-based sensors [164]; new promising neural-based approaches have been proposed that link neuromorphic systems to machine learning [165]- [169]; substantial progress has been made in the field of neuromorphic robots [170]; and we are now able to engineer both large scale neuromorphic systems (e.g., that comprise of the order of 10 6 neurons [171]) and complex multi-chip neuromorphic systems (e.g., that can exhibit cognitive abilities [20]). However, compared to the progress made in more conventional standard engineering and technology fields, the rate of progress in NE might appear to be disappointingly small.…”
Section: Challenges and Progress In Neuromorphic Engineeringmentioning
confidence: 99%
“…Many years have passed since the first publication on neuromorphic electronic systems [11], and remarkable progress has been made by the small but vibrant Neuromorphic Engineering (NE) community [162], [163]. For example the NE community has mastered the art of building real-time sensory-motor reactive systems, by interfacing circuits and networks of the type described in this paper with neuromorphic event-based sensors [164]; new promising neural-based approaches have been proposed that link neuromorphic systems to machine learning [165]- [169]; substantial progress has been made in the field of neuromorphic robots [170]; and we are now able to engineer both large scale neuromorphic systems (e.g., that comprise of the order of 10 6 neurons [171]) and complex multi-chip neuromorphic systems (e.g., that can exhibit cognitive abilities [20]). However, compared to the progress made in more conventional standard engineering and technology fields, the rate of progress in NE might appear to be disappointingly small.…”
Section: Challenges and Progress In Neuromorphic Engineeringmentioning
confidence: 99%
“…For example, Intel showed that highperformance quasi-delay-insensitive (QDI) design is sufficiently robust and effective for high performance networking chips [17]. Moreover, the challenges of managing a global clock in large neuromorphic chips, have driven IBM [18] and Stanford [19] to adopt an asynchronous mostly QDI interconnect. Other academic researchers have found that built-in flowcontrol in bundled-data network-on-chips lead to significant benefits in terms of latency and area compared to synchronous counterparts [15].…”
Section: Discussionmentioning
confidence: 99%
“…Zbieżność tej koncepcji z architekturą mózgu naturalnego stwarza możliwość zbudowania sztucznego systemu zdolnego do świadomego działania, a jego grafowa struktura dostosowana do równoległego przetwarzania informacji wzbudza nadzieję na możliwość szybkiej realizacji technicznej takiego przedsięwzięcia. Tym bardziej, że technologia dostarcza podzespołów doskonale nadających się do roli elektronicznego podłoża do zdefiniowanych w modelu Horzyka funkcji [Benjamin i in., 2014;Merolla i in., 2014]. Zaproponowany model sieci neuronowej posiada dostateczną elastyczność, aby uzupełnić go o funkcje niezbędne do tak sformułowanego zadania.…”
Section: Język Sztucznych Sieci Neuronowychunclassified